Performance measurement systems in small medium enterprises (SMEs): A practical modified framework - Muhammad Jamil, Che Zuriana; Mohamed, Rapiah (2011)
This paper reviews the literature of performance measurement systems (PMSs) in small and medium-sized enterprises (SMEs). Concern on PMSs has notably increased in the last twenty years, However, the research has been focused in large organizations. An increasing interest has just been given to develop PMSs in SMEs as the complexity and diversity of the management system in SMEs requires SMEs to have better framework to gain competitive advantages, and continuously react and adapt to external changes. This paper attempts to introduce modified PMSs models suited to the needs of SMEs. This paper contributes to the body of knowledge by identifying and developing an improved PMSs framework to be widely adopted by the SMEs.